The Influence of Financial Performance, Financial Distress, and Director Compensation on CEO Turnover: The Moderating Role of Internal Experience - Ardi, Hernando; Handoko, Jesica (E-Jurnal Akuntansi; Vol 35 No 3 (2025)DO - 10.24843/EJA.2025.v35.i03.p03, 2024)
The Chief Executive Officer (CEO) serves as the primary regulator and controller of corporate operations, with the overarching goal of maximizing firm profitability. However, when shareholders perceive the CEO’s performance as unsatisfactory, leadership changes may occur. Frequent CEO turnover within a short period can have detrimental effects on organizational stability and performance. This study investigates the impact of financial performance, financial distress, and board of directors' compensation on CEO turnover, while also examining the moderating role of internal experience. The research focuses on manufacturing firms listed on the Indonesia Stock Exchange (IDX) from 2019 to 2022. Using purposive sampling, a total of 123 firm-year observations were selected. Logistic regression was employed as the primary data analysis technique. The empirical findings reveal that financial performance—measured by current ratio (CR), return on assets (ROA), and debt-to-equity ratio (DER)—along with financial distress and the CEO’s internal experience, do not significantly influence CEO turnover. Conversely, board of directors' compensation is found to have a significant effect on CEO turnover. Furthermore, internal experience moderates the relationship between board compensation and CEO turnover, amplifying its impact. This study highlights that while financial indicators and internal experience alone do not directly influence CEO turnover, compensation structures and internal experience jointly play a critical role in shaping CEO succession decisions. Keywords: CEO Turnover; Financial Performance; Financial Distress; Board of Directors Compensation; Internal Experience.